Mechanical Relaxation-to-Rejuvenation Transition in a Zr-based Bulk Metallic Glass - M. Zhang (Nature Portfolio, 2017)
Abstract The relaxation of amorphous materials, i.e., aging, would largely endanger their performances in service. Here we report a mechanical relaxation-to-rejuvenation transition of a Zr35Ti30Be27.5Cu7.5 bulk metallic glass (BMG) in elastostatic compression at ambient temperature, thus provide an accessible way to tailor the mechanical properties of amorphous materials. To unravel the structural evolution underlying the observed transition, atomistic simulations parallel with the experimental tests on a typical model glass system Zr60Cu40 were performed, which successfully reproduced and thus upheld the experimentally observed mechanical relaxation-to-rejuvenation transition. The variations of coordination number and atomic volume during the transition are evaluated to indicate a de-mixing tendency of the constituent atoms in the rejuvenation stage. This de-mixing tendency largely explains the difference between mechanical rejuvenation and thermal rejuvenation and reveals a competitive relationship between activation enthalpy and activation entropy in the stress-driven temperature-assisted atomic dynamics of BMG, such as diffusion and plastic deformation etc.